Intellectual property : economic and legal dimensions of rights and remedies - Blair, Roger D.; Cotter, Thomas F., 1961- (Cambridge ; New York : Cambridge University Press, 2005)
This book addresses several aspects of the law and economics of intellectual property rights (IPRs) that have been underanalyzed in the existing literature. It begins with a brief overview of patents, trade secrets, copyrights, and trademarks, and the enforcement and licensing of IPRs, focusing on the remedies available for infringement (injunctions, various forms of damages, and damages calculation issues); the standard of care (strict liability versus an intent- or negligence-based standard); and the rules for determining standing to sue and joinder of defendant for IPR violations. The authors demonstrate that the core assumption of IPR regimes - that IPRs maximize certain social benefits over social costs by providing a necessary inducement for the production and distribution of intellectual products - have several important implications for the optimal design of remedies, the standard of care, and the law of standing and joinder.
Introduction -- The law and economics of IPRs -- A general theory of damages rules -- Departures from the general theory -- Liability standards for IPRs -- Who is an infringer? -- Who should be entitled to sue for infringement? -- Calculating monetary damages -- Concluding remarks.
Includes bibliographical references (p. 267-283) and index.
1
Keywords: Intellectual property -- United States; Intellectual property -- Economic aspects; Intellectual property infringement -- United States